Alexander Calder - Multum in parvo - Perl, Jed 1951-; Shapiro, Karl 1913-2000; Updike, John 1932-2009; Goldberger, Paul 1950- (Dominique Lévy, 2015)
The book also includes commissioned essays by Jed Perl, art historian and author currently at work on the first full-length biography of Alexander Calder, and Paul Goldberger, Pulitzer Prize-winning architecture critic, as well as poems by Karl Shapiro and John Updike
Published on the occasion of Alexander Calder: multum in parvo, April 22-June 13, 2015, Dominique Lévy, New York, NY
Keywords: Calder, Alexander -- 1898-1976; Ausstellungskatalog -- Dominique Lévy -- 22.04.2015-13.06.2015 -- New York, NY